Financial Risk and International Inbound Tourism: A Malaysian Illustration - Mohd Roslen, Siti Nurhidayah; Shan, Chua Mei; Zaghlol, Azlul Kalilah; Mohd Ruslan, Rafiatul Adlin Hj (Information Management and Business Review, 2023)
The impact of financial risk on inbound tourism is explored in this study by examining the effect of shocks in foreign debt level and debt service stability on the tourist arrival rate in Malaysia, based on the Theory of Planned Behavior (TPB). Quarterly data from 2010 to 2020 were obtained from multiple sources, which include the Malaysia Tourism corporate website, the official portal of the Ministry of Economy Malaysia, the Department of Statistics Malaysia, and the Federal Reserve (FRED) Economic statistical website. A VAR model was estimated, together with the Granger causality test, to identify the relationship between financial risk, control variables, and the tourist arrival rate in Malaysia. We specifically consider the effects of financial risk on estimated impulse responses and variance decompositions for the studied variables. Empirical results indicate that there is a unidirectional causality running from foreign debt level stability, debt service stability, and industrial production to tourist arrivals. In addition, there is also bidirectional causality from the effective exchange rate to tourist arrivals and from tourist arrivals to the effective exchange rate. This study is the first of its kind to explore the effect of financial risks in the context of foreign debt levels and debt service stability in Malaysia. The study emphasizes the importance of monitoring the country’s debt financing threshold to maintain financial stability, which if violated would be detrimental to tourism.